Catalytic Enantioselective Conjugate Addition of Stereodefined Di‐ and Trisubstituted Alkenylaluminum Compounds to Acyclic Enones. Issue 2 (10th December 2019) - McGrath, Kevin P.; Hubbell, Aran K.; Zhou, Yuebiao; Santos, Damián Padín; Torker, Sebastian; Romiti, Filippo; Hoveyda, Amir H.
Abstract: Catalytic enantioselective conjugate addition (ECA) reactions with readily accessible and stereochemically defined E ‐, Z ‐, di‐ and trisubstituted alkenyl aluminum compounds are disclosed. Transformations are promoted by various NHC‐copper catalysts (NHC=N‐heterocyclic carbene), which are derived from enantiomerically pure sulfonate imidazolinium salts. The desired products were obtained in up to 89% yield and >99:1 e.r.; the alkenyl moiety was transferred with complete retention of its stereochemical identity in all instances. The scope and limitations of the approach, key mechanistic attributes, and representative functionalization are presented as well. Abstract :